PENGARUH KATALIS BASA (NaOH) PADA TAHAP REAKSI TRANSESTERIFIKASI TERHADAP KUALITAS BIOFUEL DARI MINYAK TEPUNG IKAN SARDIN - Diah Probo Ningtyas (Jurnal Teknosains, 2013)
Biofuel is an alternative diesel engine fuel is produced from oils/fats of plants and animals (including the fisheries industry waste) through the esterification and transesterifiksi reactions. A transesterification is reaction to form esters and glycerol from trigliserin (fat/oil) and bioalcohol (methanol or ethanol). Transesterification is an equilibrium reaction so that the presence of a catalyst can accelerate the achievement of a state of equilibrium. Process of the transesterification reaction of sardine flour oil waste with NaOH as base catalyst in producing biofuels was conducted.The research purpose has studied the influence of NaOH concentration in transesterification process and examinate its effect on the quality of biofuels production, conversion, and physic quality. The variables that analysed was the effect of NaOH concentration as catalyst (0.5%, 1.0%, 1.5%, and 2.0% from amount of oil and methanol) in the transesterification reaction step. The result showed that the increasing NaOH concentration (0.5 - 1.5%), enhanced the biofuel conversion (%). The highest conversion of biofuels was achieved by using 1.50% NaOH (w/w) with 45.34% biofuels conversion. The major component in the biofuels was methyl palmitate (20.31%). ASTM analysis data also supported that the biofuel product was in agreement with automotive diesel fuel specification.